LEVEL OF KNOWLEDGE OF ANTIBIOTIC USAGE IN MEDICAL FACULTY STUDENTS OF UNIVERSITAS MALIKUSSALEH YEAR 2019 - sahputri, juwita; Z, Khairunnisa (Fakultas Kedokteran Universitas Malikussaleh, 2020)
Antibiotics are one of the most widely used drugs. The use of antibiotics is very widespread supported by the ease with which antibiotics are bought at pharmacies without a doctor's prescription. Antibiotics can reduce the rate of bacterial infections if used according to the right rules. The use of antibiotics without a doctor's prescription is now more widespread and has the effect of increasing the development of bacteria that are resistant to antibiotics. Knowledge of the rules of use and the mechanism of action of antibiotics is very important to be studied by health science students, especially by medical students. This study aims to determine the knowledge of the use of antibiotics among students of the Medical Study Program FK Unimal 2019 Class. This research is a descriptive study, using a cross sectional method with a total sampling of 96 respondents who met the inclusion and exclusion criteria. The results of the study are presented as univariate descriptive analysis with tables. The results of research on the level of knowledge of students of the Medical Study Program Malikussaleh University in 2019 on the use of antibiotics, there were 87.5% who had good knowledge, 12.5% moderate knowledge and did not find students who had less knowledge.Â Keywords: antibiotic, knowledge level, Unimal medical student Â